2018
DOI: 10.1002/navi.259
|View full text |Cite
|
Sign up to set email alerts
|

Ziv‐Zakai Bound for Direct Position Estimation

Abstract: Direct position estimation (DPE) has arisen as an appealing alternative to the conventional two‐step positioning (2SP) approach. The usual metric to assess the performance of estimators is the Cramér‐Rao Bound (CRB). However, the CRB is only accurate in the high signal‐to‐noise ratio (SNR) region. In the lower SNR regions, high estimation errors take place and the variance of the estimates approach the a priori domain of the parameter. The DPE approach is expected to overcome the 2SP approach in such condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The Cramér-Rao Bound can also be applied to position estimation [8]. We consider the CRB for a fixed geometry.…”
Section: S(f ) Is the Frequency Domain Representation Of S(t)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cramér-Rao Bound can also be applied to position estimation [8]. We consider the CRB for a fixed geometry.…”
Section: S(f ) Is the Frequency Domain Representation Of S(t)mentioning
confidence: 99%
“…We consider the bound for the case of the mobile station being in a deterministic position x m . The Ziv-Zakai bound for this case is given as [8]:…”
Section: B Ziv-zakai Boundmentioning
confidence: 99%
“…4) Ziv-Zakai Lower Bound Familiy Recently, based on the second order Taylor series approximation, an approximate Ziv-Zakai lower bound (ZZLB) for a deterministic parameter was derived for the TOA estimation problem [71]. An approximate ZZLB for deterministic parameters was also introduced [72]. Unfortunately, this approximation provides a lower bound on the estimation error only for unbiased estimators.…”
Section: ) Barankin Lower Bound Familymentioning
confidence: 99%
“…Such a one‐step approach – referred to as Direct Position Estimation (DPE) for reasons discussed in Section 2 – pivots the GNSS‐based localization problem, providing ways to address the challenges of conventional two‐step receivers at the expense of added computation load. The potential of the DPE approach has begun to be explored with conceptual motivations (Axelrad, Bradley, et al, 2011; Brown, 2012; Closas & Gusi‐Amigó, 2017), analytical advantages (Closas, Fernández‐Prades, & Fernández‐Rubio, 2007a, 2009a; Gusi‐Amigó et al, 2018), and demonstrated benefits of DPE‐based receivers (Chu, 2018; Dampf et al., 2017; Ng & Gao, 2016b) being presented in the literature. This work aims to support the growth of the DPE body‐of‐knowledge through a survey of DPE processing techniques, the release of open‐source parallelized DPE‐based receiver software, and a discussion of considerations for practical DPE‐based receiver design.…”
Section: Introductionmentioning
confidence: 99%